Efficient Gene Transfection through Inhibition of β‐Sheet (Amyloid Fiber) Formation of a Short Amphiphilic Peptide by Gold Nanoparticles. (10th April 2017) - Jana, Poulami; Samanta, Krishnananda; Bäcker, Sandra; Zellermann, Elio; Knauer, Shirley; Schmuck, Carsten
Abstract: The effect of citrate‐stabilized gold nanoparticles (AuNPs) on the secondary structure of an artificial β‐sheet‐forming cationic peptide has been studied. The AuNPs inhibited β‐sheet formation and led to fragmented fibrils and spherical oligomers with assembled AuNPs on their surface. Besides this structural change, the functional properties of the peptide are also different. Whereas the peptide was unable to act as a vector for gene delivery, formation of a complex with AuNPs allowed successful gene delivery into cells.